Enhancing Access to Early Intervention Services for Children with Developmental Disorders - Rasheedat Modupe Oladimeji; Habibat Bolanle Abdulkareem; Rukayat Adetoun Abdulkareem (Chalim Journal of Teaching and Learning, 2026)
Children with developmental disorders often experience delays in receiving appropriate care due to inconsistent diagnostic practices and unequal access to early intervention services. This study examined inconsistencies in diagnostic procedures, assessed the accessibility and challenges of early intervention services, and evaluated the contribution of family involvement to children’s developmental progress. A qualitative systematic review design was adopted through the analysis of empirical studies, policy documents, and program reports from diverse contexts. Data were synthesized thematically to identify recurring patterns and service gaps. Findings revealed significant disparities in diagnostic standards, unequal access to essential services, and persistent barriers including inadequate resources, limited public awareness, and cultural constraints. The review further showed that informed and actively engaged families significantly improved the effectiveness of intervention outcomes. The study concluded that standardized diagnostic frameworks and holistic family-centered approaches are essential for equitable and responsive service delivery. It was recommended that policymakers, health professionals, and families collaborate to strengthen inclusive systems that promote early detection, timely intervention, and improved developmental outcomes for children with developmental disorders.